Multiculturalism and Prior Knowledge as the Basis for Assessing Tolerance in Civic Education - Muhammad Nurman (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to assess the impact of implementing a multicultural problem-based learning model and prior knowledge on students' tolerance attitudes in the Citizenship Education course. Methodology: The sampling technique was carried out using cluster random sampling to determine the experimental and control classes. Data collection methods included tests and questionnaires. Tests were used to collect data on prior knowledge, while questionnaires were used to collect data on students’ tolerance attitudes. Data analysis was conducted descriptively and inferentially. Inferential analysis employed a two-way analysis of variance (ANOVA) 2 x 2. Main Findings: The results of the analysis indicate that the implementation of a multicultural problem-based learning model and prior knowledge affect students' tolerance attitudes in the citizenship course. Novelty/Originality of this study: The novelty of this research lies in the integration of two aspects that are rarely explicitly combined: multiculturalism as a socio-cultural framework and prior knowledge as a cognitive aspect in the assessment of tolerance attitudes. This approach produces a more comprehensive assessment instrument compared to previous studies.